ANALISIS IMPLEMENTASI HALAL VALUE CHAIN PADA UMKM MAKANAN HALAL DI KAWASAN BERENDO KOTA BENGKULU - Yosi Arisandi; Miko Polindi; Indri Apriliani (JSE: Jurnal Sharia Economica, 2026)
The purpose of this study is to explore the potential and challenges associated with the implementation of the Halal Value Chain in halal food MSMEs in Bengkulu City's Berendo Area. Although the Halal Value Chain (HVC) has not yet been fully established, the Berendo Area was chosen because it has been designated as a Halal, Safe, and Healthy Culinary Zone (Zona KHAS). This study employed a descriptive qualitative technique and field research methodology. In-depth interviews, observation, and documentation were used to gather data. Purposive sampling was used to select five MSMEs and five customers as informants. Data reduction, data presentation, and conclusion drafting were used in the data analysis process. The findings demonstrate that while all MSMEs have received halal certification, the HVC's implementation is subpar. Weaknesses in the input stage, production process, and processing and service aspects have an impact on the compliance rate, which is around 75%. The region's backing as a halal hub, growing consumer confidence, and the possibility of halal culinary tourism make the implementation of HVC extremely promising. Low halal literacy, a lack of comprehension among MSMEs, business competition, and problems with parking and guest comfort are some of the obstacles.